Women rights and EU: Gender discrimination in the fields of payment ec directives ecj decisions and the current developments in Turkey - Hoşgör, Esra (My University, 2010)
Ayrımclık Türk ve Avrupa Birliği hukuk sistemleri için kritik sorunlardan biridir. AB ayrımcılığı yasaklamak ve eşit ödeme ilkesini sağlamak için çeşitili hukuki düzenlemeler yapmıştır. Bugünün dünyasında kadın ve erkek arasındaki ücret farkları kayda değer bir mesele haline gelmiştir. Bu yüzden bu çalışmadaki amacım ayrımclık ve eşit ödeme prensibine dikkat çekmektir. AB Antlaşması madde 141 erkek ve kadın işçiler için eşit işe eşit ücret ilkesini getirmiştir. Ve AB’ de bu konularda çeşitili tüzük ve yönergeler çıkarılmıştır. Adalet Divanı kararlarıda bu konularda büyük etki yaratmıştır. Türk hukukunda İş Kanunu madde 5 bu konu ile alakalıdır. Türkiye Türk hukuk sistemi ile AB hukuku sistemini uyumlaştırma amacı ile bu alanda bazı kanuni değişiklikler yoluna gitmiştir. Bu çalışma Türkiye ve AB’nde ayrımcılık yasağı ve eşit ödeme ilkesini şekillendirmek için faydalı olmak üzere hazırlanıp bitirilmiştir.

Discrimination has been a critical problem in EU and Turkey legal systems. EU took measures to combat discrimination and provide equal pay principle. In today’s world pay differences between men and women become a significant issue. So in this work my aim was to take attention to discrimination and equal pay principle. Article 141 of EC Treaty has been a provision providing equal pay principle for men and women for equal work or work of equal value. And there have been several Regulations and Directives related to these issues. ECJ‘s case law has a major effect on these subjects. In Turkish law Labor Act Article 5 deals with this issue. And Turkey has made some changes in these fields in order to harmonize Turkish legal system to EU legal system. This work has been devised and settled so that it would be utile for shaping anti discrimination law and equal pay principle in EU and Turkey.
Keywords: Avrupa Birliği Hukuku; Ayrımcılık; Kadın Hakları